Reporting the Effect of Cell Seeding Density on Growth Pattern of Cancer Cell Lines: Cell Seeding Density and Growth Curve - Maryam Nakhjavani; Farshad H. Shirazi (Iranian Journal of Pharmaceutical Sciences, 2017)
In vitro studies on cancer cell lines still constitute a major part of cancer research. It is very important that the researchers consider the importance of basic conditions of working with different cell lines. To the best of authors’ knowledge, this study is the first one to report the effect of seeding density on the growth curve of three human cancer cell lines. These cell lines include human breast adenocarcinoma MCF-7 cell line, human ovary carcinoma A2780 cell line and human melanoma A375 cell line. The cell lines were seeded at 4 different seeding densities: 4000, 5000, 15000 and 50000 cells/cm2 of culture surface. Following seeding the cells and on daily basis, cell count was done with trypan blue assay. The experiment was done in triplicate. The growth curves of the cells were constructed using Microsoft Excel and population doubling time (PDT), lag time (LT) and saturation density (SD) were calculated. The results showed that the seeding density affects the general pattern of the growth curve. At lower seeding densities, the growth curves have a more expected pattern rather than in higher seeding densities. Also, seeding density does not affect the LT, while it has some effects on SD and PDT.